2017
DOI: 10.1371/journal.pone.0180245
|View full text |Cite
|
Sign up to set email alerts
|

Differences in serum IgA responses to HIV-1 gp41 in elite controllers compared to viral suppressors on highly active antiretroviral therapy

Abstract: Mechanisms responsible for natural control of human immunodeficiency type 1 (HIV) replication in elite controllers (EC) remain incompletely defined. To determine if EC generate high quality HIV-specific IgA responses, we used Western blotting to compare the specificities and frequencies of IgA to HIV antigens in serum of gender-, age- and race-matched EC and aviremic controllers (HC) and viremic noncontrollers (HN) on highly active antiretroviral therapy (HAART). Concentrations and avidity of IgA to HIV antige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 86 publications
0
20
1
Order By: Relevance
“…119 Furthermore, ECs have been shown to demonstrate a wider breath of HIV protein recognition and higher avidity serum IgA antibodies to gp41. 73 Surprisingly, ECs have been found to have stronger Env C1-specific IgA responses compared with noncontrollers in this recent study, which opposes the finding that IgA-C1 responses in RV144 vaccines are associated with risk. The authors go on to suggest that the specificities of anti-gp120…”
Section: Serum Anti-hiv Iga: Negative Consequencescontrasting
confidence: 84%
See 2 more Smart Citations
“…119 Furthermore, ECs have been shown to demonstrate a wider breath of HIV protein recognition and higher avidity serum IgA antibodies to gp41. 73 Surprisingly, ECs have been found to have stronger Env C1-specific IgA responses compared with noncontrollers in this recent study, which opposes the finding that IgA-C1 responses in RV144 vaccines are associated with risk. The authors go on to suggest that the specificities of anti-gp120…”
Section: Serum Anti-hiv Iga: Negative Consequencescontrasting
confidence: 84%
“…71 HIV also preferentially infects activated HIV-infected CD4 + T cells, 72 thus it has been hypothesized that this may contribute to the decrease in CD4 + T cell help and class switching of anti-HIV IgA, while having less of an effect upon humoral responses to other infectious diseases. 51,73 As HIV also preferentially infects activated CD4 + T cells, dysfunctional class switch recombination may be targeted to specific activated antigen-specific T cells. The precise mechanisms behind why this skewed IgA/IgM isotype ratio occurs in HIV infection for certain microbial antigens, but not others, warrant further investigation.…”
Section: Iga and Its Complex Role In Hiv 729mentioning
confidence: 99%
See 1 more Smart Citation
“…The protective potential of serum IgA has been suggested in elite controllers (individuals that spontaneously control HIV‐1 viremia) in whom higher titers of HIV‐1‐specific serum IgA have been observed compared with HIV‐1 progressors . In vitro studies have demonstrated that monoclonal IgA has the capacity to activate antibody functions against HIV‐1 antigens (ADCC and phagocytosis) .…”
Section: Virusesmentioning
confidence: 99%
“…The avidity of serum IgG Abs to gp140 C.1086 or gp120 1157ipd3N4 protein was measured using NaSCN displacement ELISA as described (67). The avidity index was calculated by dividing the concentration of antibodies in wells treated with 1.5 M NaSCN for 10 minutes at 37°C by the concentration of antibodies in untreated wells.…”
Section: Ab Aviditymentioning
confidence: 99%